GPR52 regulates cAMP in T cells but is dispensable for encephalitogenic responses - Krieg, Paula F.; Sonner, Jana K.; Kurelic, Roberta; Engler, Jan Broder; Scharenberg, Marlena F.; Bauer, Simone; Nikolaev, Viacheslav O.; Friese, Manuel A. (Frontiers in Immunology, 2023)
G-protein coupled receptors (GPCR) regulate 3',5'-cyclic adenosine monophosphate (cAMP) levels in T cells. cAMP as ubiquitous second messenger is crucial for adequate physiology of T cells by mediating effector T cell (Teff) function as well as regulatory T cell (Treg)-mediated immunosuppression. Several GPCRs have been identified to be crucial for Teff and Treg function. However, the role of the orphan, constitutively active Gs-coupled GPCR GPR52 is unknown. Here we show that GPR52 regulates cAMP levels in T cells but does not affect T cell function. We found that stimulation of transfected HEK cells or primary T cells with a GPR52 agonist results in a rise of intracellular cAMP. However, neither Gpr52 deficiency nor pharmacological modulation of GPR52 by antagonists or agonists affected T cell activation, differentiation, and proliferation or Treg-mediated immunosuppression. Moreover, Gpr52 deletion did not modify the clinical disease course of experimental autoimmune encephalomyelitis (EAE). Our results demonstrate that a modulation of cAMP levels in T cells does not inevitably result in altered T cell function. While we could not identify an obvious role of GPR52 in in vitro T cell assays and in vivo CNS autoimmunity, it might regulate T cell function in a different context or affect the function of other GPR52-expressing cells.